QUALITY OF EGG FOR CONSUMPTION FROM DIFFERENT PRODUCERS IN THE MARKETS IN R. MACEDONIA: 2. HOUGH UNITS AND YOLK COLOR - Kocevski Dragoslav1, Nedeljka Nikolova2, Vukovic Vlado1, Bunevski Gjoko1, Dzabirski Vladimir1, Gjorgievski Srecko1, Porcu Koco1 (3rd INTERNATIONAL SYMPOSIUM FOR AGRICULTURE AND FOOD – ISAF 2017, 2017)
Eggs from 7 different brands offered to the supermarket chains in R. Macedonia were tested for meeting the minimum quality requirements defined by the Law. Egg size (egg weight in g) as well as internal quality traits (Hough Units that unbiased expressed egg “freshness” and Yolk color expressed as Roche leader scale from 1-14) were analyzed on 140 eggs. Each group was randomly represented by 10 M-weight class and 10 L-weight class eggs from each of the 7 brands, purchased directly from the supermarket shelf and analyzed the same day after the purchasing. Egg quality was analyzed in the Laboratory for control of the marketing quality of eggs at the Institute for animal biotechnology on the Faculty of agricultural science and food, using computerized equipment for measuring egg internal quality (Egg Multi Tester EMT 5200, Robotmation Co. Ltd., Tokyo, Japan). Eggs from analyzed brands in general meat the required marketing standards in respect to the analyzed parameters: egg albumen height or freshness (average = 61.56 and 58.75 Hough Units) and yolk color (average = 12.48 and 12.28 units of Roche scale) for L and M weight class, respectively. Only eggs from brand No. 4 does not fulfill the minimum required marketing standards in respect of the Hough Units (42.49 and 40.89 Hough Units) for M and L weight class, respectively. Additionally, eggs from brand No. 5 have average value below (51.95 Hough Units) the minimal required standard for freshness of 55 Hough units defined in the Law for quality of agricultural products and average weight for L class lower (62.04g) than the minimum requirement of 63g for this weight class.
Keywords: brands, eggs for consumption, markets, Hough units, yolk color.